Global Economic Prospects and the Developing Countries 1998-99 - World Bank (Washington, DC: World Bank, 2019)
The global economic crisis that began in Thailand on July 2, 1997, dominates the world economic scene for more than a year. Global Economic Prospects and the Developing Countries 1998/99 lays out the anatomy of the crisis, and assesses both the short- and long-term outlooks for the world economy and developing countries in the aftermath of the crisis. There is not unanimity on many key issues, yet Chapters 2 and 3 represent the World Bank’s interim research findings. The report aims to identify areas where there is and where there is not a consensus; and when there is not, trying to identify the reasons, whether it is alternative models of the economy or interpretations of the evidence.